Analysis of factors influencing excellent female 100-meter race score and establishment of evaluation system - Lu, G. (Proceedings of the International Conference on Future Computer Science and Education, 2011, 2011)
This paper has screened out major factor indices reflecting the excellent female 100-meter race score through investigation and expert interview, mathematical statistics. Predicated models were established for body training level and dedicated item score. Their relationship was also analyzed from multi-level, multi-perspectives through the combination of athletic measurement and evaluation, sport physiology, systematic theory, cybernetics and characteristics of items. The result shows that 1) The five major inspecting indices for 100-meter races for female athletes i.e. flying run 30m, stride length, stride frequency, ten-class standing long jump and 300m, have closely relation with the special item results. 2) Establishment of regression equation to forecast the results of China national master sportswomen, one class 100-meter races for female athletes. 3) Three kinds of evaluation methods and criteria for Chinese elite female 100-meter runners in this paper provide evidence for evaluating performance of physical training comprehensively. The three kinds of methods and evaluation criteria include comprehensive developing level, the equilibrium degree and adaptation degree of comprehensive developing level of physical training and special performance.